2020
DOI: 10.14336/ad.2020.0111
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Mechanisms and Potential Therapeutic Targets of Pulmonary Arterial Hypertension: A Review

Abstract: Pulmonary arterial hypertension (PAH) is a progressive cardiovascular disease characterized by pulmonary vasculature reconstruction and right ventricular dysfunction. The mortality rate of PAH remains high, although multiple therapeutic strategies have been implemented in clinical practice. These drugs mainly target the endothelin-1, prostacyclin and nitric oxide pathways. Management for PAH treatment includes improving symptoms, enhancing quality of life, and extending survival rate. Existing drugs developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 126 publications
0
30
0
Order By: Relevance
“…Although LIRI could be reduced by anti-inflammatory, antioxidant and anti-apoptotic action [ 21 ], the development and treatment of LIRI are also affected by its comorbidities, especially when combined with PAH. PAH is characterized by pulmonary vasoconstriction and pulmonary vascular remodeling, narrowing and occlusion of small pulmonary arteries, and increased vascular resistance [ 22 ], which affect the reperfusion and aggravate the inflammatory response and lung injury. The endothelial cell dysfunction and in situ thrombosis caused by PAH increase thrombosis during lung ischemia [ 10 , 23 ], which also reduces reperfusion and aggravates the inflammatory response and lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…Although LIRI could be reduced by anti-inflammatory, antioxidant and anti-apoptotic action [ 21 ], the development and treatment of LIRI are also affected by its comorbidities, especially when combined with PAH. PAH is characterized by pulmonary vasoconstriction and pulmonary vascular remodeling, narrowing and occlusion of small pulmonary arteries, and increased vascular resistance [ 22 ], which affect the reperfusion and aggravate the inflammatory response and lung injury. The endothelial cell dysfunction and in situ thrombosis caused by PAH increase thrombosis during lung ischemia [ 10 , 23 ], which also reduces reperfusion and aggravates the inflammatory response and lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the lung tissues from the patients with PAH had increased levels of infiltrating Th2 cells, Tregs, and mast cells and decreased levels of macrophages. PAH is associated with immune dysregulation characterized by increased perivascular infiltration of T cells and mast cells and dysfunction of Th2 cells and Tregs [ 3 ]. Pathogenic Th2 cells have been shown to promote pulmonary artery muscularization by secreting IL-13 [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Strategies targeting crucial pathways, including nitric oxide, prostacyclin, RhoA/Rho kinase pathway modulators, and endothelin-1, have been used in patients with PAH [ 2 ]. Although the current PAH-targeted therapies can improve the quality of life and reduce the hospital readmission rate, the 5-year mortality rate of patients with PAH remains approximately 50% [ 3 ]. Therefore, a deeper understanding of the molecular mechanisms underlying PAH may enable the development of novel drugs to improve the survival rate of patients.…”
Section: Introductionmentioning
confidence: 99%
“…HPASMC proliferation was prevented by imatinib, a potent inhibitor of platelet-derived growth factor receptor beta (PDGFRβ) and other protein kinases involved in PAH 10 . Demonstration of the effectiveness of imatinib in our model is critical as the drug, evaluated in a phase 3 clinical study (IMPRES), is currently undergoing further trials to establish an e cacious dose amid concerns about its safety and tolerability 28 . BMPR2 knockdown did not affect endothelial barrier function in PA-on-a-chip, in contrast to the observations made in conventional cell culture systems 18 .…”
Section: Discussionmentioning
confidence: 99%